ANALYSIS OF THE PRODUCTION OF INTELLECTUAL PROPERTY IN THE NATIONAL UNIVERSITY OF CALLAO THROUGH ITS PATENTS, UTILITY MODELS AND INVENTION - IPINCE-ANTUNEZ, DANIEL (2024)
EMERGING ECONOMIES FACE PROBLEMS IN THE ADMINISTRATION AND ENFORCEMENT OF INTELLECTUAL PROPERTY PROTECTION IN THEIR COUNTRIES, ESPECIALLY AT THE UNIVERSITY LEVEL. GIVEN THAT PATENTS ARE AN IMPORTANT PART OF INTELLECTUAL PROPERTY RIGHTS, THEIR STUDY ALLOWS US TO UNDERSTAND THE ROLE OF UNIVERSITIES IN THE DIFFUSION OF TECHNOLOGY IN SOCIETY; HOWEVER, THE CHARACTERIZATION AND PRODUCTION OF PATENTS IN LATIN AMERICAN UNIVERSITIES, ESPECIALLY IN PERU, HAS BEEN LITTLE STUDIED. THE OBJECTIVE OF THIS ARTICLE IS TO FULLY CHARACTERIZE THE PATENTS GRANTED AND APPLIED FOR, TAKING INTO ACCOUNT THE CURRENT CONTEXT TO DETERMINE THEIR PROGRESS, THE LINES OF TECHNOLOGICAL INTEREST AND THE COLLABORATION NETWORKS AT THE NATIONAL UNIVERSITY OF CALLAO. THE RESEARCH IS DESCRIPTIVE, DOCUMENTARY AND LEGAL INFORMATION IN THE FIELD OF INTELLECTUAL PROPERTY HAS BEEN TRACKED, ESTABLISHING A CONCEPT CONTEXTUALIZED TO THE CURRENT SITUATION. THE PATENT STATISTICS PROVIDED IN THE ARTICLE SHOW THAT, DESPITE THE CONTINUOUS GROWTH THAT HAS BEEN SEEN FROM 2018 TO THE PRESENT IN PATENT PRODUCTION, CONSTANT PATENT GUIDANCE SHOULD BE GIVEN TO STUDENTS, GRADUATES, AND FACULTY OF THE NATIONAL UNIVERSITY OF CALLAO TO INCREASE THEIR PARTICIPATION. IN ADDITION, TO PROMOTE THE CREATION OF PATENTS THROUGH MULTIDISCIPLINARY RESEARCH THAT HELPS THEM TO UNDERSTAND IN A PRACTICAL WAY THE PROCEDURE THEY MUST FOLLOW TO PATENT. © 2024 LATIN AMERICAN AND CARIBBEAN CONSORTIUM OF ENGINEERING INSTITUTIONS. ALL RIGHTS RESERVED.